Self-Compassion and Spiritual Well-Being Among Employees in Educational Institutions - Tandukar, Rinisha; Shah, Nitesh Kumar; Adhikari, Bibhav (Journal of Innovation in Academia, 2024)
This study investigates the relationship between self-compassion and spiritual well-being among employees of educational institutions in the Kathmandu Valley. A descriptive research design was adopted, utilizing convenience sampling to collect cross-sectional data from 171 respondents via an online Google Form. Data analysis was performed using correlation and chi-square tests in SPSS version 23. The results indicated that most respondents demonstrated high levels of self-compassion and spiritual well-being, with no significant differences across demographic factors. A moderate positive correlation of 0.514 was found between self-compassion and spiritual well-being. In terms of self-compassion, mindfulness ranked highest, followed by self-kindness, with common humanity ranking lowest. Regarding spiritual well-being, the communal domain ranked the highest, followed by the environmental, personal, and transcendental domains, respectively. It is recommended that educational institutions focus on these high-ranking factors to enhance employee satisfaction.